What Education Should Be Provided to Early Childhood in The Millennial Era? - Heru Sriyono; Nur Rizkiyah; Sigit Widiyarto (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
Early childhood education requires good and regular management and knowledge that is adapted to the millennial era. The method used is a qualitative method with data collection techniques through observation, interviews, documentation and literature studies and triangulation techniques are used. The respondents were 8 people (teachers, school principals and parents). The study was conducted from January to June 2022. The results of the study stated that basic education that must be mastered includes moral/religious abilities, physical motor skills, arts/languages, emotional and cognitive abilities. These abilities are implemented based on good education management, and are supported by millennial century skills such as computer introduction to simple coding for students. Learning in the millennial era demands changes in educational management that are adapted to technology. Application of wireless communication technology and virtual reality for preschool education information will be realized. A complete change in the way of preschool education is needed and ultimately cultivating children who are morally, intellectually, physically and artistically qualified.